Communication strategies in the mental development of soldiers for strengthening religious moderation in the military environment - Andi Hasriani; Badruddin Kaddas; St. Samsuduha; Maryati Mallongi; Andi Paduppai (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2026)
Da'wah communication plays an important role in fostering moderate religious attitudes amid the challenges of extremism, radicalism, and intolerance in plural societies. In military institutions, strengthening religious moderation is essential to maintain soldiers’ professionalism, social stability, and national commitment. This study aims to analyze the strategies of da'wah communication in soldiers’ mental development to strengthen religious moderation within the military environment. This research employs a descriptive qualitative method using a da'wah communication approach. Data were collected through observation, in-depth interviews, and documentation, and were analyzed through data reduction, data display, and conclusion drawing. The findings reveal that da'wah communication strategies in soldiers’ mental development are implemented through religious lectures, interfaith dialogue, and the internalization of national and historical values using persuasive, rational, and humanistic approaches. These strategies contribute to shaping inclusive and tolerant religious attitudes while strengthening national integration within the military environment. Theoretically, this study enriches the field of Islamic communication by demonstrating that da'wah communication in military settings functions not only as a medium for transmitting religious values but also as an integrative instrument that connects religiosity, nationalism, and military professionalism in strengthening religious moderation. ***** Komunikasi dakwah memiliki peran penting dalam membangun sikap keagamaan yang moderat di tengah tantangan ekstremisme, radikalisme, dan intoleransi dalam masyarakat plural. Dalam lingkungan militer, penguatan moderasi beragama menjadi bagian penting untuk menjaga profesionalitas prajurit, stabilitas sosial, serta komitmen kebangsaan. Penelitian ini bertujuan menganalisis strategi komunikasi dakwah dalam pembinaan mental prajurit untuk memperkuat moderasi beragama di lingkungan militer. Penelitian ini menggunakan metode kualitatif deskriptif dengan pendekatan komunikasi dakwah. Pengumpulan data dilakukan melalui observasi, wawancara mendalam, dan dokumentasi yang kemudian dianalisis melalui reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa strategi komunikasi dakwah dalam pembinaan mental prajurit dilakukan melalui ceramah keagamaan, dialog lintas agama, serta internalisasi nilai-nilai kebangsaan dan sejarah perjuangan bangsa dengan pendekatan persuasif, rasional, dan humanis. Strategi tersebut berkontribusi dalam membentuk sikap keagamaan yang inklusif, toleran, serta memperkuat integrasi nasional di lingkungan militer. Secara keilmuan, penelitian ini memperkaya kajian komunikasi Islam dengan menunjukkan bahwa komunikasi dakwah dalam lingkungan militer tidak hanya berfungsi sebagai sarana transmisi nilai-nilai keagamaan, tetapi juga sebagai instrumen integratif yang menghubungkan nilai religiusitas, nasionalisme, dan profesionalisme keprajuritan dalam penguatan moderasi beragama.